2017
DOI: 10.1155/2017/1053617
|View full text |Cite
|
Sign up to set email alerts
|

The Versatile Effects of Dihydromyricetin in Health

Abstract: Dihydromyricetin is a flavonoid isolated from Ampelopsis grossedentata, which is traditionally used in China. Dihydromyricetin exhibits health-benefiting activities with minimum adverse effects. Dihydromyricetin has been demonstrated to show antioxidative, anti-inflammatory, anticancer, antimicrobial, cell death-mediating, and lipid and glucose metabolism-regulatory activities. Dihydromyricetin may scavenge ROS to protect against oxidative stress or potentiate ROS generation to counteract cancer cells selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 68 publications
1
54
0
Order By: Relevance
“…Conventionally, DMY is used as antioxidant, antimicrobial, antiviral and anti-inflammatory agent. Current research has also shown its therapeutic benefits for the treatment of various chronic diseases such as cancer, diabetes, obesity, alcohol use disorders and metabolic or neuro imbalance (Kou & Chen, 2012;Li et al, 2017).…”
Section: Biological Activities Of Dmymentioning
confidence: 99%
“…Conventionally, DMY is used as antioxidant, antimicrobial, antiviral and anti-inflammatory agent. Current research has also shown its therapeutic benefits for the treatment of various chronic diseases such as cancer, diabetes, obesity, alcohol use disorders and metabolic or neuro imbalance (Kou & Chen, 2012;Li et al, 2017).…”
Section: Biological Activities Of Dmymentioning
confidence: 99%
“…Flavonoids predominantly existed in A. gressedentata , which accounted for 430 mg/g dry weight (He, Yang, Pei, & Peng, 2004). Flavonoids have many pharmacological functions, such as renal and liver protection, as antioxidants, anti‐inflammatory, and antivirus molecules, and as free radical scavengers and immunity enhancers (Li et al., 2017). Long‐term toxicity studies of A. grossedentata extract reported no adverse effects associated with its application, thus highlighting its potential for use in humans (Zhou et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is found in the Ampelopsis species, and Chinese vine tea (Ampelopsis grossedentata) is used for DHM isolation. DHM possesses numerous pharmacological activities, including antioxidant, anticancer, antimicrobial and hepatoprotective 144 . The consumption of DHM was found to reduce UVBinduced photoaging in mice 145 .…”
Section: Dihydromyricetinmentioning
confidence: 99%